(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Electrical impedance spectroscopy has a high potential for monitoring and characterizing samples, e.g., biological cells. The technique is highly sensitive but artefacts often disturb it. This study discusses problems for miniaturization of the measurement volume needed to observe single cells in a 3D printed 4T setup. There is a capacitive artefact between 1 Hz – 1 kHz introduced by the distortion of the electric field due to fringing effects. Proposed solution for reducing distortion: use of thinner measurement electrodes.